A New Nanomaterial Based on Extracellular Vesicles Containing Chrysin-Induced Cell Apoptosis Through Let-7a in Tongue Squamous Cell Carcinoma - Yang, Zhijing; Liu, Da; Zhou, Hengzong; Tao, Boqiang; Chang, Lu; Liu, Huimin; Luo, Haoming; Wang, Dongxu; Liu, Weiwei (Frontiers in Bioengineering and Biotechnology, 2021)
Although the therapeutic strategy showed significant improvement, the therapeutic effect was poor on metastases in tongue squamous cell carcinoma (TSCC) which is the most malignant tumor in the head and neck . Chrysin, like the flavonoids, plays an anti-tumor role through regulating the expression of ncRNAs in many kinds of cancers. Compared to flavonoids, gold nanoparticles (AuNPs) provide a novel insight into inhibiting cancer cell growth via photothermal therapy (PPT) which irradiated by near infrared radiation (NIR). However, most flavonoids and gold nanoparticles lake of specificity of tumor in vivo. The extracellular vesicles (EVs) which were abundant with ncRNAs, are isolated from the cellular supernatant fluid and have the ability to carry on drugs or nanoparticles to improve specificity. In the present study, we aimed to synthesize a new nanomaterial based on EVs containing chrysin and analyzed cell apoptosis in TSCC cells. Our results demonstrated that EVs-Chrysin were isolated from SCC9 cells that were treated with chrysin. To improve the therapeutic effect, AuNPs were carried by EVs-Chrysin (Au-EVs). Compared to BGC823 and HCC-LM3 cells, the uptake of Au-EVs were specific in SCC9 cells. Moreover, Au-EVs combined with NIR enhanced cell apoptosis in TSCC cells. To confirm the role of miRNAs in cell apoptosis, the differentially expressed miRNAs between EVs-Con and EVs-Chrysin were screened by RNA-seq. The results revealed that the let-7a-3p, which acts as the tumor suppressor, was upregulated in EVs-Chrysin compared to EVs-Con. Thus, let-7a-3p was screened in the apoptosis pathway that was associated with the p53 protein. Further, compared to the Con group, Au-EVs combined with the NIR group effectively inhibited tumor growth in vivo via the increased the expression of let-7a-3p. Together, as a new nanomaterial, Au-EVs induced cell apoptosis and inhibited tumor growth through regulating let-7a-3p expression in TSCC.